Efektivitas Pengawasan dan Kepatuhan Pelaporan Pertanggungjawaban Keuangan Dana Kapitasi JKN Puskesmas - Moa, Januarius; Yuneti, Katharina; Lamawitak, Paulus Libu (Universitas Nusa Nipa Maumere, 2026)
This study aims to evaluate the effectiveness of supervision conducted by the Sikka District Health Office regarding the financial accountability reporting compliance of JKN Capitation Funds at Community Health Centers, with a primary focus on understanding the implemented supervisory models and identifying factors that inhibit the effectiveness of oversight and reporting compliance. The research methodology employed is descriptive qualitative, utilizing data collection techniques such as in-depth interviews with key informants, direct observation, and document analysis of accountability reports. The findings reveal that the supervisory mechanisms established by the Health Office through quarterly evaluations and data reconciliation have operated systematically to minimize recording errors; however, the overall effectiveness is still hindered by low compliance at the Health Centers level regarding reporting timeliness. This non-compliance leads to obstructed comprehensive oversight, the risk of delayed capitation fund disbursements for subsequent periods, and an increased potential for audit findings by regulatory bodies. Consequently, this study suggests the necessity of enhancing supervisory capacity at the Health Centers level and strengthening preventive guidance functions by the District Health Office to ensure better financial accountability.